Analysis of the effect of a novel therapeutic for type 2 diabetes on the proteome of a muscle cell line. Issue 1 (12th December 2015) - Young, Pamela A.; Leonard, Siobhán; Martin, Darren S. D.; Findlay, John B. C.
Abstract : Elevated serum retinol‐binding protein (RBP) concentration has been implicated in the development of insulin resistance and type 2 diabetes. Two series of small molecules have been designed to lower serum levels by reducing secretion of the transthyretin–RBP complex from the liver and enhancing RBP clearance through the kidney. These small molecules were seen to improve glucose and insulin tolerance tests and to reduce body weight gain in mice rendered diabetic through a high fat diet. A proteomics study was conducted to better understand the effects of these compounds in muscle cells, muscle being the primary site for energy expenditure. One lead compound, RTC‐15, is seen to have a significant effect on proteins involved in fat and glucose metabolism. This could indicate that the compound is having a direct effect on muscle tissue to improve energy homeostasis as well as a whole body effect on circulating RBP levels. This newly characterized group of antidiabetic compounds may prove useful in the treatment and prevention of insulin resistance and obesity.